2022
DOI: 10.1002/smtd.202200208
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Controllable Eu‐MOFs through Machine Learning Technology: Application for High Sensitive Ions and Small‐Molecular Identification

Abstract: high-resolution, especially in the solid state or high concentration liquid states. [5][6][7] Dong et al. constructed two Ln-MOFs {[Ln(H 3 L)(H 2 O)] • 7H 2 O} n (Ln = Eu and Tb, H 3 L = 5-(3',5'-dicarboxylphenyl)picolinic acid), and utilized these two kinds of Ln-MOFs to detect the Fe 3+ and chromate ions. [8] And the detection limits of Fe 3+ / CrO 4 2-/Cr 2 O 7 2are 0.67/0.53/0.32 × 10 −6 m for europium-based metal-organic frameworks (Eu-MOFs) and 1.26/0.75/0.57 × 10 −6 m for Tb-MOFs, respectively. Cui et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Previous works have shown that the Eu can be used as the metal node and 5-bop and 1,3-BDC can be used as the mixed ligands to form a repeated and ordered 3D spatial structure . Generally, the discrete carboxylate group of 1,3-BDC can be used to link the Eu 1 and Eu 2 atoms alternately and form 1D chains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works have shown that the Eu can be used as the metal node and 5-bop and 1,3-BDC can be used as the mixed ligands to form a repeated and ordered 3D spatial structure . Generally, the discrete carboxylate group of 1,3-BDC can be used to link the Eu 1 and Eu 2 atoms alternately and form 1D chains.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, Eu-MOFs dissolved in ethanol exhibit the highest intensities in the wavelengths of 591, 615, and 699 nm, but the intensity of Eu-MOFs dissolved in ethanol in a wavelength of 734 nm is quite lower than those in N -hexanol, DMF, and glycerol. Previous works have shown that although the steady PL intensities of Ln-MOFs affected by various solvents, ions, and small-molecule solutions, their 3D structures can still be preserved. Relevant works have also pointed out that the fluorescence intensity decrease phenomenon of Eu-MOFs in the static quenching state can be summarized as the 5 D 0 → 7 F J ( J = 0, 1, 2, 3, and 4) transitions of Ln 3+ ions, the energy transfer between the Ln-MOFs and solutions, the facilitation of the porous structure of Ln-MOFs on the combination of the Lewis acid ions and the pyridine Lewis base functionality of Ln-MOFs, and the weak effect of ions-O interactions. ,, Herein, it can be found in Figure J that the time-solved PL intensities of Eu-MOFs in the organic solution, such as ethanol, DMF, glycerol, and N -hexanol, are lower than that of Eu-MOFs in the water. However, their steady PL intensities of Eu-MOFs in Figure I are higher than of Eu-MOFs in the water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradient Boosted Decision Tree (GBDT) is also called as Multiple Additive Regression Tree (MART), which is also a decision tree‐based algorithm like RF (Figure 2C). 47,48 But the “boosting thought” decides that these two algorithms work in different ways. The boosting method trains the base classifier in series, and there is dependence between each base classifier.…”
Section: Typical Machine Learning Algorithms In Electrochemical Energ...mentioning
confidence: 99%
“…Random Forest (RF) and Extreme Gradient Boosting (XGBoost) are two of the numerous algorithms widely implemented in MOF-related fields. They were proved to perform well in predicting adsorption and diffusion properties of various chemical species [35][36][37][38][39][40][41][42] , electronic and force field parameters 43,44 , and catalytic abilities including carbon fixing and photodegradation 45,46 .…”
Section: Introductionmentioning
confidence: 99%